Controlled decoration of nanoceria on the surface of MoS2 nanoflowers to improve the biodegradability and biocompatibility in Drosophila melanogaster model. (14th May 2022) - Murugan, Chandran; Sundararajan, Vignesh; Mohideen, Sahabudeen Sheik; Sundaramurthy, Anandhakumar
Abstract: In recent years, nanozymes based on two-dimensional (2D) nanomaterials have been receiving great interest for cancer photothermal therapy. 2D materials decorated with nanoparticles (NPs) on their surface are advantageous over conventional NPs and 2D material based systems because of their ability to synergistically improve the unique properties of both NPs and 2D materials. In this work, we report a nanozyme based on flower-like MoS2 nanoflakes (NFs) by decorating their flower petals with NCeO2 using polyethylenimine (PEI) as a linker molecule. A detailed investigation on toxicity, biocompatibility and degradation behavior of fabricated nanozymes in wild-type Drosophila melanogaster model revealed that there were no significant effects on the larval size, morphology, larval length, breadth and no time delay in changing larvae to the third instar stage at 7–10 d for MoS2 NFs before and after NCeO2 decoration. The muscle contraction and locomotion behavior of third instar larvae exhibited high distance coverage for NCeO2 decorated MoS2 NFs when compared to bare MoS2 NFs and control groups. Notably, the MoS2 and NCeO2 -PEI-MoS2 NFs treated groups at 100 μ g ml −1 covered a distance of 38.2 mm (19.4% increase when compared with control) and 49.88 mm (no change when compared with control), respectively. High-resolution transmission electron microscopy investigations on the new born fly gut showed that the NCeO2 decoration improved the degradation rate of MoS2 NFs. Hence, nanozymes reported here have huge potential in various fields ranging from biosensing, cancer therapy and theranostics to tissue engineering and the treatment of Alzheimer's disease and retinal therapy.